Suggestopedia Method on Improving Students’ Reading Comprehension - Vebriana Setia Deny; Syamsul Bahri Ys; Dian Fajrina (Research in English and Education Journal, 2017)
This research is intended to find out whether Suggestopedia method improved students’ reading comprehension. This research was conducted at SMPN 8 Banda Aceh. The sample was taken by random sampling of the students of class VIII-1. The technique of data collection, the researcher used pre-test, treatment and post-test. The materials used in the test were narrative texts. The reading comprehension which tested was main idea, detail information, vocabulary and reference. The researcher used one group pre-test and post-test design. The tests consisted of 10 multiple choice questions of narrative texts. The technique of data analysis, the researcher used statistical formula. The mean score of pre-test was (53.18) and the post-test was (79.09). The finding showed that the improvement of the mean was 25.91. The critical value of 0.05 significant level was 2.080 and degree of freedom was 21. T-test 4.197 was higher than t-table (2.080). As a result, Suggestopedia method can improve the students’ reading comprehension in narrative text particularly at the VIII-1 of SMPN 8 Banda Aceh.